THE INFLUENCE OF SAFETY TRAINING AND SAFETY LEADERSHIP ON SAFETY PERFORMANCE AT PT. ANTAM TBK UBPN KOLAKA - Laura Septiani; Almansyah Rundu Wonua; Agus Zul Bay (LPPM UNIVERSITAS BINA INSAN, 2026)
Purpose: This study aims to examine the influence of Safety Training and Safety Leadership on Safety Performance at PT. ANTAM (Persero) Tbk UBPN Kolaka, Indonesia. Research Methodology: This study employed a quantitative explanatory design involving 165 employees selected through purposive sampling. Data were collected using structured questionnaires and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS. Results: Safety Training has a positive and significant effect on Safety Performance, indicating that continuous training improves employees' safety knowledge, awareness, and safe work practices. Safety Leadership also has a positive and significant effect and shows a stronger influence than Safety Training. This finding indicates that leaders' commitment, communication, and active participation in safety management are essential for strengthening safety culture and encouraging employees to consistently perform safe work behaviors. Conclusions: The findings indicate that improving Safety Performance requires the integration of effective Safety Training and strong Safety Leadership. While training develops employees' safety competencies, leadership reinforces organizational safety values and creates a sustainable safety culture, making it the dominant factor in improving safety performance in mining operations. Limitations: This study was conducted in a single mining company with 165 respondents; therefore, the findings should be generalized with caution. Contributions: This study enriches occupational safety and health research by empirically comparing the effects of Safety Training and Safety Leadership on Safety Performance using PLS-SEM in the Indonesian mining sector. The findings highlight the dominant role of Safety Leadership and provide practical guidance for developing integrated safety management strategies to improve safety performance in high-risk industries.